Vernetzungsstrukturen lexikografische Daten und ihre XML-basierte Modellierung - Müller-Spitzer, Carolin (HERMES - Journal of Language and Communication in Business, 2007)
Lexicographic data are normally linked with each other in a complex manner. Especially, within the electronic lexicographic context, the following issues are addressed: How to encode these cross-reference structures so that both the lexicographers‘ editorial work with the linking-up is easy to handle and the options of the presentation are adequately ﬂexible. The objective of this paper is to elucidate the presentation of an XML-modelling of cross-reference structures as part of a complete modelling concept. Thereby, the modelling potential of the XML-connected standard XLink and a new lexicographic concept will be brought together with cross-project guidelines for the modelling of link-structures.